2020
DOI: 10.1007/s10909-020-02364-y
|View full text |Cite
|
Sign up to set email alerts
|

Extending KIDs to the Mid-IR for Future Space and Suborbital Observatories

Abstract: The galaxy evolution probe (GEP) is a concept for a probe-class space observatory to study the physical processes related to star formation over cosmic time. To do so, the mid-and far-infrared (IR) spectra of galaxies must be studied. These mid-and far-IR observations require large multi-frequency arrays, sensitive detectors. Our goal is to develop low NEP aluminum kinetic inductance detectors (KIDs) for wavelengths of 10-400 μm for the GEP and a pathfinder long-duration balloon (GEP-B) that will perform precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 9 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…Simulations indicate that this geometry achieves a peak single-polarization absorptivity of just over 70% near 10 μm for R □ ¼ 0.2 to 0.8 Ω, bracketing the range expected for a 40-nm Al film. Perido et al 63 presented dark measurements of Fig. 7 Far-IR detector technology has made considerable progress toward larger, more sensitive arrays over the past decade.…”
Section: Kinetic Inductance Detectors and Readout Electronicsmentioning
confidence: 99%
“…Simulations indicate that this geometry achieves a peak single-polarization absorptivity of just over 70% near 10 μm for R □ ¼ 0.2 to 0.8 Ω, bracketing the range expected for a 40-nm Al film. Perido et al 63 presented dark measurements of Fig. 7 Far-IR detector technology has made considerable progress toward larger, more sensitive arrays over the past decade.…”
Section: Kinetic Inductance Detectors and Readout Electronicsmentioning
confidence: 99%
“…The KIDs developed for TIM will also form the basis for the FIFI+LS blue channel detectors but will use a modified absorber and optical coupling scheme appropriate for the shorter wavelengths. Recent simulation work and initial testing was presented by Perido et al 21 in a study for detectors for the galaxy evolution probe (GEP). 22 Their work addresses KIDs designed for wavelengths between 10 and 100 μm.…”
Section: Kids Arraysmentioning
confidence: 99%
“…Their simulation work has shown that thin aluminum film may be patterned on a silicon substrate to produce good optical absorption at wavelengths as short as 10 μm. The short meander design studied by Perido et al 21 used a 200-nm wide absorber line that is interrupted with a meander to increase the resistance per unit length while simultaneously introducing a distributed capacitance to compensate for the accompanying distributed inductance. For backside illumination, this design achieves a dualpolarization efficiency of 58% over the 10-to 30-μm band, a fractional bandwidth larger than that of the 51-to 125-μm FIFI+LS blue channel spectral range.…”
Section: Kids Arraysmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding polarization sensitivity, earth-based instruments such as NIKA2 [9] use an external polarizer that separates the two linear polarizations into two independent arrays based on a Hilbert fractal structure. On the other hand, some additional works have focused on the development of dual-polarization LEKIDs demonstrating simultaneous orthogonal polarization sensitivity in the millimeter and submillimeter wave ranges [8], [14]. However, very little has been done in developing dualpolarization LEKIDs in the W-band.…”
mentioning
confidence: 99%